Karakteristik dan Tingkat Kecukupan Energi Pasien Penyakit Infeksi dan Degeneratif yang Dirawat Inap di Rumah Sakit - Annisa Rizkiriani; Rina Martini; Sesar Husen Santosa; Ridwan Siskandar (PUSAT SAINS INDONESIA, 2021)
The patient's energy adequacy level can reduce morbidity and mortality, as well as accelerate the healing process and reduce the length of time hospitalized for patients. The purpose of this study was to determine the characteristics and level of energy adequacy of patients with infectious and degenerative diseases who were hospitalized at the hospital. The design of this study was coss sectional. The number of samples was 30 hospitalized patients whose consumption was observed for 3 days. samples were selected purposively in hospitals in Bogor and Jakarta. Statistical analysis using Mann Whitney test, pearson correlation regression, and stepwise regression using Microsoft Excel and Minitab. The results showed that there was a relationship between age, nutritional status, blood pressure, and body temperature with the type of disease. More than one-third of the patient's energy adequacy level was in the severe deficit category. The determinant factors for the type of disease are age and the level of energy adequacy.